Strategic Social Choice Stable Representations of Constitutions - Peleg, Bezalel; Peters, Hans.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This monograph studies representations of effectivity functions by game forms that are at least Nash consistent, which means that they have a Nash equilibrium for any profile of preferences. In the second part the focus is on social choice functions that admit a strong Nash equilibrium resulting in the sincere outcome. A central interpretation of an effectivity function is that it models a constitution.
Representations of constitutions -- to Part I -- Constitutions, effectivity functions, and game forms -- Nash consistent representations -- Acceptable representations -- Strongly consistent representations -- Nash consistent representation through lottery models -- On the continuity of representations of constitutions -- Consistent voting -- to Part II -- Feasible elimination procedures -- Exactly and strongly consistent representations of effectivity functions -- Consistent voting systems with a continuum of voters.
Keywords: Economics; Mathematics; Economics, Mathematical; Social sciences -- Methodology; Economics/Management Science; Game Theory/Mathematical Methods; Game Theory, Economics, Social and Behav. Sciences; Economic Theory; Methodology of the Social Sciences